1974
DOI: 10.1083/jcb.63.2.414
|View full text |Cite
|
Sign up to set email alerts
|

IN SITU LOCALIZATION OF GLOBIN MESSENGER RNA FORMATION

Abstract: In the accompanying paper (1) in situ hybridization of globin DNA copy (cDNA) to fetal liver was used to elucidate the process of globin messenger RNA (mRNA) formation in erythroid precursor cells. The essential conclusions were also confirmed by conventional hybridization studies. In the present paper, the same dual approach is applied to a different experimental system in which hemoglobin synthesis in Friend virus-transformed mouse cells is induced by treatment with dimethylsulfoxide (DMSO) (2). The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1976
1976
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…It has previously been demonstrated that BUdR interferes with the DMSOinduced differentiation of Friend leukaemia cells (Ostertag et al, 1973; and that this inhibition results from interference with the accumulation of globin mRNA (Conkie et al, 1974;Preisler et al, 1973). These observations, taken together with those reported here, strongly suggest that these leukaemic cells continue to synthesize and accumulate globin mRNA after removal of DMSO from the culture medium and that iinterference with this process inhibits differentiation during secondary culture in DMSO-free medium.…”
supporting
confidence: 78%
“…It has previously been demonstrated that BUdR interferes with the DMSOinduced differentiation of Friend leukaemia cells (Ostertag et al, 1973; and that this inhibition results from interference with the accumulation of globin mRNA (Conkie et al, 1974;Preisler et al, 1973). These observations, taken together with those reported here, strongly suggest that these leukaemic cells continue to synthesize and accumulate globin mRNA after removal of DMSO from the culture medium and that iinterference with this process inhibits differentiation during secondary culture in DMSO-free medium.…”
supporting
confidence: 78%
“…Interestingly, some other proteins implicated in oncogenesis can also damage or kill specific cells (21,64,66,72,77 (25). Our preliminary studies suggest that the SFF-PU.1 virus differs from a Gag-Myb-Ets-encoding virus (2,62) 13,1993 stages of leukemic progression could be recapitulated in their cultures. As they reported, we have also observed rapid proliferation and terminal differentiation of Epo-independent CFU-E in cultures infected with polycythemic strains of SFFV (31a).…”
Section: Pu1 Immortalizes Erythroblastsmentioning
confidence: 87%
“…VOL. 13,1993 5672 SCHUETZE ET AL. [44,48]), the encoded helper-free viruses amplify by a back-and-forth (ping-pong) process of infection (6,38).…”
Section: -Globin Probe Consisted Of the Hindlll Fragment (Probe B)mentioning
confidence: 99%
“…The cell lines used were Hep3B and HepG2 (human hepatoma), MRC5 (human fetal lung fibroblast), 1BR3 (human skin fibroblast), U937 (human monocyte/macrophage), (monkey renal fibroblast), LLC-PK1 (pig renal epithelium), RAEC (rat aortic endothelium), a23 (Chinese hamster lung fibroblast), Kl Cell Cultures and cultured as specified by the supplier. Cells from other sources were a23 (11), RAEC (29), and MEL (30). The only nonadherent cells were MEL and U937.…”
Section: Methodsmentioning
confidence: 99%